How Do Specialized Units Affect the Outputs of Police Organizations?: Investigating the Effect of Community Policing Units on Community Policing Activities in Local Police Departments - Namgung, Hyon (2013)
A review of modern police history shows the trend of increased division of labor within police agencies. However, police organizations are often criticized for creating specialized police units when they are faced with specific problems or are not effectively tackling local problems. Other challenges from within the profession include potential inter-unit conflicts or indifference of officers from other units that may hinder program implementation by specialized units. The present study looked into the changing characteristics of specialized units within police departments between 2000 and 2007. This research also examined whether creation of specialized community policing units (CP Units) influences the community policing activities performed by police agencies. The results show that wide variations exist in the operation of specialized police units among police agencies. Specifically, the increase of some specialized units (e.g., cyber-crime, hate crime, missing child, and terrorism units) seems to reflect social changes and police departments’ responses to tackle diverse problems arising from such changes. Also, linear panel analysis indicates that police agencies with CP Units were more likely to produce outputs in each element of community policing (i.e., community engagement, problem-solving, and organizational transformation). In other words, the creation of specialized units may lead to the increase of outputs that the units are intended and designed to produce